Aktivitas Mikofagi dari Kelas Agaricomycetes di Hutan Kampus Institut Pertanian Bogor, Indonesia - Dianita, Ici; Syahbani, Noer; Putra, Ivan Permana (Jurnal Ilmu Kehutanan, 2025)
Macrofungi are a nutraceutical food containing high protein, low fat, and are rich in minerals that play an important role in animal physiology, particularly as food supplements because of their distinctive aroma. This research aimed to provide information on the macroscopic and microscopic characters of several macrofungi from the Agaricomycetes consumed by animals, and to describe their antibacterial potentials. This research employed opportunistic sampling, mushroom identification and description, proximate analysis, and antibacterial assays. A total of seven mushrooms of the Agaricomycetes were described, namely Lentinus sajor-caju, Gymnopilus sp., Marasmius sp., Phallus indusiatus, Panus lecomtei, Termitomyces sp., and Schizophyllum commune. Lentinus sajor-caju had carbohydrate, fiber, protein, fat, ash, and moisture contents of 72.02%, 30.03%, 11.63%, 1.37%, 4.26 %, and 10.74%, respectively. The antibacterial assay of L. sajor-caju indicated that both 0.8 mg/ml and 1 mg/ml concentrations showed no significant difference in activity. However, both exhibited potent inhibitory effects against Candida albicans. Lentinus sajor-caju extract inhibited Enteropathogenic Escherichia coli (EPEC) at a concentration of 5 mg/ml. In comparison, a dose of 0.8 mg/ml effectively suppressed the growth of Methicillin-resistant Staphylococcus aureus (MRSA). This current research provided a basic framework for future mycophagy analysis and bioprospection in Indonesia.